Seminavis exigua sp. nov. (Bacillariophyceae), a new small diatom from southern Fujian Province, China. Issue 2 (3rd April 2019) - Chen, Changping; Zhuo, Suqing; Wang, Zhen; Gao, Yahui; Zhang, Jun; Sun, Lin; Liang, Junrong; Li, Xuesong; Zhang, Jiawei; Li, Lang
Abstract : This study describes the diatom species Seminavis exigua sp. nov., collected from an intertidal sandy beach in southern Fujian Province, China. A detailed description is given based on light and scanning electron microscopy observations. Seminavis exigua possesses small valves and the diagnostic features of this species include slit-like areolae, accessory rib on the primary side, raphe located very close to the ventral margin, and one to two rows of lineolae present on the ventral sides. Its morphology is comparable to that of similar species such as Seminavis strigosa (Hustedt) Danielidis & Economou-Amilli, Seminavis macilenta (Gregory) Danielidis & Mann, Amphora cymbellamphora Cholnoky, Amphora exilitata Giffen, and Amphora tenerrima Aleem & Hustedt.